Impacts of the Russia-Ukraine War price shocks on the Bangladesh economy: A general equilibrium analysis - Chowdhury, Tahreen Tahrima; Dorosh, Paul A.; Islam, Rizwana; Pradesha, Angga (International Food Policy Research Institute, 2023)
The spike in global commodity prices caused by the Russia-Ukraine war has had major adverse impacts on many developing countries, including Bangladesh, that still depend heavily on energy and food imports. Although the Bangladesh economy has rebounded after the COVID-19 pandemic, the latest global trade shock has threated to increase food insecurity and poverty. This study utilizes the Bangladesh RIAPA economywide model to assess the impact of increases in global commodity prices and explores potential policy interventions to reduce negative impacts. Simulation results show that increases in international commodity prices create a GDP loss of 0.36 percent and an increase of three million in the number of poor (mainly rural poor). Energy price shocks account for most of this decline in real GDP (0.28 percent). The fertilizer subsidy helps spur agriculture production which leads to an increase in crop GDP by 0.78 percent and total agricultural GDP by 0.43 percent. Changes in policy could help mitigate the effects of these price shocks. In particular, petroleum subsidies would help increase production in both agriculture and services, leading to a 0.3 percent increase in household consumption, considerably more than the gain under a targeted cash transfer policy of equal cost. However, given that the petroleum subsidy does not specifically target the poor, it only reduces poverty by a fraction of what a targeted cash transfer would. Moreover, as illustrated by the experiences of other countries, increases in a fuel subsidy, once introduced, are likely to be very difficult to reverse. This suggests that if the major policy goal is to reduce poverty, a direct cash transfer would be more effective than the other policy options considered here. Combining these policies, however, would be even more effective than any single intervention, reducing poverty incidence by around 2.5 million people, and thereby preventing nearly all of the potential increase in poverty resulting from global price shocks.